In silico study of chikungunya polymerase, a potential target for inhibitors - Ghildiyal, Ritu (Virusdisease, 2019)
Non-structural protein 4 (nsP4) polymerase of chikungunya virus (CHIKV) has a crucial role in genome replication and hence could act as a promising target for novel therapeutics. Though, nsP4 is important in viral life cycle, but it is less explored as therapeutic target. The catalytic core of nsP4 Polymerase includes conserved GDD motif which is present not only across different CHIKV strains but also across other Alphaviruses. This emphasizes the uniqueness and importance of this motif in the functioning of nsP4 polymerase and hence, we focused on GDD motif for docking of drug molecules. Herein, a model of nsP4 polymerase was developed using Swiss Model, validated by Ramachandran plot and molecular dynamic simulation. Molecular docking was performed using LeadIT FlexX flexible docking module with FDA approved drug molecule library. On the basis of flexX score, top 5 leads with flexX scores − 33.7588, − 30.2555, − 29.6043, − 28.916 and − 28.5042 were selected. The bonding pattern of these leads were analysed in discovery studio and were further screened on the basis of molecular dynamic simulation studies. Simulation analysis revealed that only the top lead, Mitoxantrone Hydrochloride which is an anticancer drug and is currently indicated in leukemias and lymphomas interacted favourably and stably with nsP4. Our findings suggest that Mitoxantrone Hydrochloride can be a potential novel inhibitor of CHIKV polymerase and should be further validated by in vitro assays. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13337-019-00547-0) contains supplementary material, which is available to authorized users.